Disease burden and attributable risk factors of lip and oral cavity cancer in China from 1990 to 2021 and its prediction to 2031 - Yu, Zhengrong; Ma, Xiangming; Xiao, Hanyu; Chen, Yihong; Wu, Yuhang; He, Jing; Cheng, Peiyu (Frontiers in Public Health, 2024)
Aims This study addresses the essential need for updated information on the burden of lip and oral cavity cancer (LOC) in China for informed healthcare planning. We aim to estimate the temporal trends and the attributable burdens of selected risk factors of LOC in China (1990–2021), and to predict the possible trends (2022–2031). Subject and methods Analysis was conducted using data from the Global Burden of Disease study (GBD) 2021, encompassing six key metrics: incidence, mortality, prevalence, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). Absolute number and age-standardized rates, alongside 95% uncertainty intervals, were computed. Forecasting of disease burden from 2022 to 2031 was performed using an autoregressive integrated moving average (ARIMA) model. Results Over the observed period (1990–2021), there were notable increases in the number of deaths (142.2%), incidence (283.7%), prevalence (438.0%), DALYs (109.2%), YLDs (341.2%), and YLLs (105.1%). Age-standardized rates demonstrated notable changes, showing decreases and increases of −5.8, 57.3, 143.7, −8.9%, 85.8%, and − 10.7% in the respective metrics. The substantial majority of LOC burden was observed among individuals aged 40–79 years, and LOC may exhibit a higher burden among males in China. From 2022 to 2031, the age-standardized rate of incidence, prevalence, and YLDs of LOC showed upward trends; while mortality, DALYs, and YLLs showed downward trends, and their estimated values were predicted to change to 2.72, 10.47, 1.11, 1.10, 28.52, and 27.43 per 100,000 in 2031, respectively. Notably, tobacco and high alcohol use emerged as predominant risk factors contributing to the burden of LOC. Conclusion Between 1990 and 2021, the disability burden from LOC in China increased, while the death burden decreased, and projections suggest these trends will persist over the next decade. A significant portion of this disease burden to modifiable risk factors, specifically tobacco use and excessive alcohol consumption, predominantly affecting males and individuals aged 40–79 years. Attention to these areas is essential for implementing targeted interventions and reducing the impact of LOC in China.